Simple and low-cost preparation of carbon-coated titanium dioxide via hydrothermal method - Leny Yuliati, Leny Yuliati (Trans Tech Publications, 2014)
In the present study, carbon-coated titanium oxide (C-TiO2) was synthesized by hydrothermal method using dichloromethane as the novel low-cost carbon source. XRD patterns revealed that after purification method, only diffraction peaks of anatase TiO2 can be observed. On the other hand, the formation of carbon can be suggested from DR UV-visible spectrum and SEM image, which showed the additional of absorption band in the visible region and the successful formation of carbon that grew both on the surface with a unique noodle-like structure and surroundings of the TiO2 with non-uniform bulk structure, respectively.